The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1029/jc085ic03p01591
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the complex refractive index and size distribution of atmospheric particulates from bistatic‐monostatic lidar and solar radiometer measurements

Abstract: A method is presented for inferring both the size distribution and the complex refractive index of atmospheric particulates from combined bistatic-monostatic lidar and solar radiometer observations. The basic input measurements are spectral optical depths at several visible and near-infrared wavelengths as obtained with a solar radiometer and backscatter and angular scatter coefficients as obtained from a bistatic-monostatic lidar. The spectral optical depth measurements obtained from the radiometer are mathem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Only one day, 5 April, when the extinction was very low, yielded a high real component (1.54) consistent with ammonium sulfate and silica which are so frequently named as chief aerosol constituents. The imaginary component estimates determined from the data (average of 0.004) are in agreement with values obtained for the 500-700 nm wavelength range from a number of other desert aerosol experiments ( e g , De Luisi et al, 1970;Grams et al, 1974;Lindberg and Laude, 1974;Spinhirne et al, 1980). Although imaginary indices in the range of 0.001-0.01 do not correspond to any specific substance commonly associated with atmospheric aerosols, the occurrence of values in t h s range is possibly a result of small amounts of carbon mixing with otherwise very weakly absorbing particles (Lindberg and Gillespie, 1977;Ackerman and Toon, 1981).…”
Section: Electron Microscope Analysissupporting
confidence: 74%
See 2 more Smart Citations
“…Only one day, 5 April, when the extinction was very low, yielded a high real component (1.54) consistent with ammonium sulfate and silica which are so frequently named as chief aerosol constituents. The imaginary component estimates determined from the data (average of 0.004) are in agreement with values obtained for the 500-700 nm wavelength range from a number of other desert aerosol experiments ( e g , De Luisi et al, 1970;Grams et al, 1974;Lindberg and Laude, 1974;Spinhirne et al, 1980). Although imaginary indices in the range of 0.001-0.01 do not correspond to any specific substance commonly associated with atmospheric aerosols, the occurrence of values in t h s range is possibly a result of small amounts of carbon mixing with otherwise very weakly absorbing particles (Lindberg and Gillespie, 1977;Ackerman and Toon, 1981).…”
Section: Electron Microscope Analysissupporting
confidence: 74%
“…Table 3 lists the aerosol extinction to backscatter ratio, S,, mixing layer height, mixing layer optical depth and total optical depth (actually optical depth to a height of 19.3 km) associated with each of the extinction profiles. The majority of the extinction profile retrievals yielded fairly low extinction standard deviations ( -$-15%) for the mixing layer, which is an indication that the requirements that horizontal homogeneity in / 3, and S, be constant with height were reasonably well met (Spinhirne et al, 1980 (Shaw, et al, 1973;King et al, 1980). The solar radiometer optical depth measurements provide a cross check to verify the lidar extinction retrieval.…”
Section: Electron Microscope Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigators have attempted to estimate this quantity, and found that the real and imaginary in dices of refraction were typically within the range of 1.45*1.55 and 0.005*0.02, respectively, for the tropospheric aerosols (e.g. Grams et al, 1974;Patterson et al, 1977;Reagan et al, 1980;Tanaka et al, 1983). The value of refractive index, m = 1.50-0.0li was assumed in this study.…”
Section: Vertical Profiles Of Optical Thickness and Size Distributionmentioning
confidence: 99%
“…The differences observed could be attributed to the non-homogeneity of the atmosphere and possibly some residual contamination by high altitude cirrus clouds (probable in the case for the sunphotometer measurements). The AOD profile was inferrred using the assumption of a lidar ratio (extinction/backscattering) of 30 (Reagan et al, 1980;Ansmann et al, 1992). This typical value for rural aerosol (Evans, 1988) may be appropriate for the Egert site by reason of the relatively low AOD values recorded (see Fig.…”
Section: Intercomparison Of Parameters With Other Methodsmentioning
confidence: 99%